2005
DOI: 10.1212/01.wnl.0000151854.85743.c7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI measurement of superior cerebellar peduncle in progressive supranuclear palsy

Abstract: The authors propose that together with other radiologic features of progressive supranuclear palsy (PSP) such as midbrain atrophy, a visual assessment of the superior cerebellar peduncle may help increase the clinical diagnostic accuracy in PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
116
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 25 publications
13
116
0
Order By: Relevance
“…In agreement with previous findings, PSP cases showed SCP values significantly different from PD, MSA-c and MSA-p 10 . Morphometric values of the middle cerebelar peduncles had the greatest practical value.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous findings, PSP cases showed SCP values significantly different from PD, MSA-c and MSA-p 10 . Morphometric values of the middle cerebelar peduncles had the greatest practical value.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, conventional magnetic resonance imaging (MRI) revealed important characteristic findings that can be used in clinical practice to differentiate among parkinsonian syndromes 5 . Objective quantifications of midbrain and pons using linear, surface and volumetric measurements have been reported before [6][7][8][9][10] . In these studies, two-point comparisons were made correlating each parkinsonian syndrome and PD.…”
mentioning
confidence: 99%
“…25 Future studies may investigate whether DTI can detect preclinical degeneration in the SN and serve as a predictive test of PD. In addition, although previous studies show promise in using DTI to differentiate PD from atypical parkinsonism, [26][27][28] large scale studies that use DTI in comparison with the gold standard of diagnosis by a movement disorders neurologist in different patient cohorts are needed. The effects of disease progression and medication intervention on DTI-based measures also need to be delineated.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies 21,22 also demonstrated abnormally increased ADC ave in the thalamus in comparison with that in healthy subjects but with a single large region of interest. Padovani et al 21 found abnormally decreased FA in the bilateral posterior thalamic radiations and anterior thalamus.…”
Section: Discussionmentioning
confidence: 70%
“…32 Our findings in the primary motor area are also consistent with the results of other imaging studies. 21,22,27,33 These abnormalities in multiple areas of the mo- tor circuit may help explain motor dysfunctions such as kinetic apraxia, frequently observed in patients with PSP. 34 ADC ave abnormalities were not found in the putamen, despite its involvement in PSP.…”
Section: Discussionmentioning
confidence: 99%